Penggunaan Media Quizizz pada Elemen Pengawasan Teknik Konstruksi dan Perumahan - Adrian Ridha Daniswara; Agus Wiyono (Jurnal Kajian Pendidikan Teknik Bangunan, 2024)
This research aims to produce quizizz learning media on the elements of construction and housing engineering supervision. The quizizz learning media in question is media that contains material and questions in it. This research is a development research using the ADDIE model which consists of 5 stages, namely the Analysis stage (analysis), Design stage (design), Development stage (development), Implementation stage (implementation), and Evaluation stage (evaluation). The data collection technique used in this research is through a questionnaire method. This technique involves respondents, namely media experts, material experts from subject teachers at SMKN 1 Sidoarjo, and students of class XI Construction and Housing Engineering SMKN 1 Sidoarjo. The data analysis technique used is descriptive analysis technique. The results of this study indicate (1) The feasibility of learning media used to get an average score from both validators is 77% with a very valid category. (2) Learning outcomes obtained by researchers get an average score in one class meeting 1 and 2, namely 81. Then students declared complete a total of 29 students or 81%. As for students who did not complete a total of 7 students or 19%. Based on these results it can be concluded that the use of quizizz media on engineering elements of construction and housing is feasible to use..